Feedback Strategies for Essays with Islamic Content: A Qualitative Study of Faculty at Islamic Higher Education - Noviyanti, Sari Dewi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
This qualitative study provides insight into the methods of providing feedback employed by ten faculty members from three higher education institutions in Indonesia when evaluating student papers containing Islamic content. This research provides insight into a significant gap in understanding how to provide feedback when the professor has no formal background in Islamic educational tradition. The study uses interpretive phenomenological analysis to analyze semi-structured interviews with the participants. Once their interviews were transcribed, the interviews were analyzed using thematic analysis. The analysis highlighted three fundamental dimensions to teacher experiences: (1) professional challenges when engaged with Islamic content including, difficulty in recognizing Islamic content and feeling less than authoritative, (2) teacher adaptive coping strategies including collaborating with consultation networks and resource utilization including digital tools for reference and academic resources support in providing feedback. The participants demonstrated impressive adaptability for developing innovative pedagogical approaches while initially struggling with ambiguity and challenges to their professional identity. This study adds to the growing literature on culturally responsive pedagogy and religious literacy in higher education contexts, and has provided practical recommendations for professional faculty development and institutional support systems. This study has provided insight-based recommendations for improving the quality of education within religiously diverse educational contexts.